2019
DOI: 10.1186/s12888-019-2327-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of path-oriented psychological self-help interventions to improve mental health of empty-nest older adults in the Community of China

Abstract: BackgroundChina has the world’s largest aging population and the number of empty-nest older adults is on the rise. In comparison to the aging population in general, empty-nest older adults have a lower level of subjective well-being and poorer mental health status due to a lack of emotional support from their children. The aim of this study is to conduct an empirical study to evaluate the efficacy of the ‘Path-oriented Psychological Self-help Intervention’ (P-oPSI) led by nurses on the mental health of empty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
1
13
1
3
Order By: Relevance
“…Accordingly, attention must be paid to the mental health of the elderly, especially for those suffering from critical illnesses. Our research also showed that, contrary to traditional thinking [ 67 , 68 ], education, living status, number of diseases have nothing to do with the patients’ depression. Self-rated health status is a subjective indicator, and often used to describe patients’ health status, which is similar to the CESD scale.…”
Section: Discussioncontrasting
confidence: 54%
“…Accordingly, attention must be paid to the mental health of the elderly, especially for those suffering from critical illnesses. Our research also showed that, contrary to traditional thinking [ 67 , 68 ], education, living status, number of diseases have nothing to do with the patients’ depression. Self-rated health status is a subjective indicator, and often used to describe patients’ health status, which is similar to the CESD scale.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding is in line with Wang. 17 The reason is that living alone is a critical health risk factor. The pressure of living alone has many components, such as psychological pressure, economic pressure, and social communication pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 400 participants met the inclusion criteria, and 44 participants, due to a sudden illness, withdrew their consent to participate during the interview (effective response rate 89%). Inclusion criteria were that participants: (i) had been settled in a rural area for at least 1 year; (ii) were aged 60 years or over; 1,17 (iii) had never had or no longer have a partner, spouse, child, without a nanny, live apart from spouse or children, or live alone at home; and (iv) agreed to participate in the study. Exclusion criteria were older adults who: (i) were suffering from a severe disease, such as severe heart failure, renal failure, lung disease, liver disease, or malignant tumors; and (ii) were disoriented, deaf‐mute, had Alzheimer's disease or suffered from mental illness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, approaches to help mitigate the negative impact of the COVID-19 pandemic on older people with previous mental health disorders are warranted. Interventions should focus on multiple components, including emotional, spiritual, social, and physical support to meet the various health needs of the elderly [ 53 - 55 ]. Internet-based interventions have demonstrated the potential to support the self-management of mental health conditions and could provide people access to information and tools during COVID-19 restrictions [ 56 - 58 ].…”
Section: Discussionmentioning
confidence: 99%